Assessment of village health sanitation and nutrition committee under NRHM in Nainital district of Uttarakhand - Semwal, V; Jha, S K; Rawat, CMS; Kumar, S; Kaur, A (Indian Journal of Community Health, 2013)
Background: The Village Health Sanitation and Nutrition Committee (VHSNC) is one of the major initiatives under National Rural Health Mission (NRHM) to decentralize and empower local people to achieve NRHM goal. Limited studies have been conducted to assess the VHSNC in India. Objective: To assess the composition of VHSNC and find out the deviations, if any, from the prescribed framework of guidelines, awareness of VHSNC members about their roles and to assess the functioning of VHSNC. Methodology: The cross-sectional study was carried out from July 2012 to June 2013 in two selected blocks (out of eight) in Nainital district of Uttarakhand. A total of 18 VHSNCs were studied, nine from Haldwani and nine from Bhimtal covering 48 revenue villages, 31 in Haldwani and 17 in Bhimtal block respectively. Out of 139 members in 18 VHSNC, 110 members were interviewed. Results: Mean age of the study subjects was 39.01 ± 8.5 years. Out of the 110 members studied maximum 73 (66.4 %) were female and 37 (33.6%) were males. Maximum subjects, 35 (32.8%) were qualified up to intermediate followed by 29 (26.4%) graduates. Maximum 78 (70.9%) participants belonged to Others (General) category, 30 (27.3%) belonged to scheduled caste and only two (1.8%) belonged to OBC category. There were no subjects belonging to scheduled tribe. Out of the 110 members interviewed there were 18 (16.4%) Gram Pradhans, 10 (9.1%) Female Health Workers, 20 (18.2%) ASHAs and 15(13.6%) Anganwadi Workers. There was very low awareness among the members about role of the committee. Maximum, 93 responses were for cleaning village environment which were given by all 18 Gram Pradhans, 16 ASHAs and ward members.